Determinan Kepuasan Kerja serta Implikasinya Terhadap Kinerja Tenaga Kesehatan di Rumah Sakit Umum Mulya Tangerang - Ananto, Tri (Media Riset Bisnis Ekonomi Sains dan Terapan, 2023)
The purpose of this study is to examine the phenomena that occur in a company, by testing several variables that affect the phenomenon in question, namely to determine the effect of transformational leadership, organizational culture, and work motivation, on job satisfaction, as well as its implications on employee performance. health at Mulya General Hospital. The research method used in this research is descriptive quantitative analysis method and is causal. Research data obtained from the distribution of questionnaires, which will then be processed through data processing methods with SPSS version 23.0. The sample in this study amounted to 100 people using the probability sampling method and taking a representative sample of the population whose samples were used or taken from a population that truly represents the existing population. The results of this study indicate that organizational culture and work motivation have a positive and significant effect on job satisfaction to improve the performance of health workers, but transformational leadership has a negative and insignificant effect on job satisfaction. Then organizational culture, work motivation, and job satisfaction, have a positive and significant effect on performance, but transformational leadership has a negative and significant effect on the performance of health workers.Keywords: Transformational Leadership, Organizational Culture, Work Motivation, Job Satisfaction, Performance.